Chapter 11: Parliamentary Devolution and Māori Self-Governance - Durie, Mason (Ngā Kahui Pou Launching Maori Futures, 2013)
By 2051 the ethnic Maori population will almost double in size to close to a million, or twenty-two percent of the total New Zealand population. Even more dramatically, by 2051 thirty-three percent of all children in the country will be Maori?' This substantial change in our society will have major implications for Maori and wider society. Professor Durie discusses traditions and customs and addresses contemporary needs in order to build development strategies for the launch of the Maori population into the new millennium.
Keywords: crown policy; parliament; rangatiratanga; self-governance

Standing for Mana - Cleave, Peter (Campus Press, 2012)
Keywords: elections; government; government relations; kāwanatanga; mana party; parliament; political activity

A Genealogy of Indigenous Resistance - Hokowhitu, Brendan (Indigenous Identity and Resistance: Researching the Diversity of Knowledge, 2010)
Brings together the work of scholars working in Canada, New Zealand and the Pacific in an exploration of the multifaceted nature of indigenous studies and the concept of indigenous studies as an academic discipline. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: activism; ethnic identity; government; iwi taketake; land march; parliament; rangahau māori; resistance; tāngata whenua

An Imbalance of Powers: Maori Land Claims and an Unchecked Parliament - Charters, Claire (Cultural Survival, 2010)
Aotearoa/New Zealand is not known for egregious breaches of indigenous peoples’ rights. Nonetheless, New Zealand’s legal system is ineffective at implementing international and domestic laws that protect the rights of Maori. This has been seen most starkly in the Foreshore and Seabed Act of 2004, which had the effect of extinguishing Maori aboriginal title to the foreshore and seabed areas and was passed despite almost universal Maori opposition.
Keywords: civil Rights; constitution; crown policy; foreshore and seabed act 2004; parliament; tiriti o waitangi/treaty of waitangi; treaty settlements

Maori and Parliament: Diverse Strategies and Compromises - Bargh, Maria (Huia Publishers, 2010)
New Zealand is at a watershed in its constitutional and political arrangements. There are three events looming in the short term which suggest that the status of Māori in Parliament is in for significant challenge.The first is the impending review of constitutional issues and the Māori seats as part of the National Party–Māori Party ‘Relationship and Confidence and Supply Agreement’.Secondly, the proposed referendum on the future of the mixed member proportional system (MMP) could also have significant implications for Māori.Finally, the longer term question of whether New Zealand should become a republic continues to haunt New Zealand’s political imagination, and would also necessitate lengthy debates about the place of New Zealand’s constitutional arrangements in relation to Māori rights and Te Tiriti o Waitangi.Māori and Parliament provides a comprehensive and enlightening context for understanding both the historical and contemporary relationship between Māori and Parliament and highlights many of the issues which would arise in any discussion of New Zealand constitutional reform.Māori and Parliament is a collection of nineteen presentations and papers from twenty-one academics, political commentators and current and former parliamentarians and is the result of the Māori and Parliament conference held at Parliament in May 2009.Contributors include Georgina Beyer, Hon. Simon Bridges, Damian Edwards, Te Ururoa Flavell, Dr Janine Hayward, Colin James, Shane Jones, Basil Keane, Hon. Sir Douglas Kidd, Professor Steven Levine, Sir Ngatata Love, Hon. Nanaia Mahuta, Sir Tipene O’Regan, Professor Nigel Roberts, Prof. Ann Sullivan, Metiria Turei, Hon. Tariana Turia, Dr Charlotte Williams, Dr John Wilson, Prof. Whatarangi Winiata and Dr Maria Bargh.
Keywords: kāwanatanga; legislative; māori politicians; māori seats; parliament; political parties